O12 Early-onset obesity is associated to birth weight, sedentary habits and the components of the pediatric metabolic syndrome - Zelmira Guntsche; Cecilia Miorin; María Julieta Pomilio; Federico Breyer; Laura Cestino; Fernando Saravi (Revista de la Sociedad Argentina de Diabetes, 2020)
Introduction: Obesity complications appear early in children. Their frequency varies with the severity of the body fat accumulation and its distribution. Birth weight (BW), the early onset of diabetes and sedentism could aggravate metabolic risk.